2005
DOI: 10.1111/j.1949-8594.2005.tb18131.x
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Spanners as Bridges of Student and School Discourses in an Urban Science and Mathematics High School

Abstract: A key to improving urban science and mathematics education is to facilitate the mutual understanding of the participants involved and then look for strategies to bridge differences. Educators need new theoretical tools to do so. In this paper the argument is made that the concept of “boundary spanner” is such a tool. Boundary spanners are individuals, objects, media, and other experiences that link an organization to its environment. They serve critical communicative roles, such as bridges for bringing distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…We identified manifestations of this agency with all of the teachers. We referred to these manifestations as boundary activities and artifacts (Buxton et al 2005). Boundary activities were small things that these teachers did to advocate for science within and beyond their school.…”
Section: Resourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified manifestations of this agency with all of the teachers. We referred to these manifestations as boundary activities and artifacts (Buxton et al 2005). Boundary activities were small things that these teachers did to advocate for science within and beyond their school.…”
Section: Resourcesmentioning
confidence: 99%
“…They became boundary activities (Buxton et al 2005) aimed at moving their colleagues toward more progressive schooling Discourses. Wenger (1998) provides us with another way to conceptualize the potential of the teachers' practices and boundary activities.…”
Section: Reform As Ongoing Accomplishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this concept of ''self-ness'' many researchers have explored issues of identity development through an analysis of discourse-how people construct or content their identities through the use of language, or how the (particular) use of (certain) language contributes to the construction of people's identities in various social contexts (e.g., Lacasa, del Castillo, García-Varela, 2005). Numerous studies have confirmed that the process of identity development at the individual level is a social process (Buxton, Caroline, & Caroline, 2005;Jenson, De Castell, & Bryson, 2003), which features language as a key element (Bucholtz & Hall, 2005).…”
Section: Theoretical Framework: Bakhtin's Theory Of Language and Idenmentioning
confidence: 96%
“…Il peut s'agir, par exemple, d'un schéma technique permettant à différents corps de métiers de se coordonner dans la conception d'une machine ou encore d'une base de données partagée par différents acteurs d'une entreprise. Dans la continuité de cette idée, certains acteurs aux expertises plus horizontales que verticales ont un rôle déterminant dans les activités se situant aux frontières sociales, par leurs capacités à tisser des liens entre des groupes différents, à assurer des processus de transposition et à diffuser de nouveaux outils, pratiques ou connaissances d'un contexte à un autre (Buxton, Carlone, et Carlone, 2005;Wenger, 1998). Cette distinction entre expertise verticale et horizontale, proposée par Engeström (1987), renvoie, pour la première, à celle d'un spécialiste d'un domaine restreint, dont la figure s'est beaucoup dévelop-pée dans nos sociétés modernes caractérisées par une forte division du travail.…”
Section: Approche Théoriqueunclassified